IMPLEMENTATION OF GOVERNMENT OVERSIGHT FUNCTIONS RELATED TO CHILD FRIENDLY GREEN OPEN SPACE IN GRESIK REGENCY - Amir, Nabbilah; Adlansyah, Burhan (Warmadewa Press, 2021)
Gresik Regency is known as a maritime and broad industrial area, regarding how the implementation of actions in the aspect of supervision carried out by Gresik District Government agencies related to the existence of a Child Friendly Green Open Space. The aim of this research is to see if green open space in Gresik Regency is suitable in terms of child-friendly standards. The research method used is empirical juridical. The results showed that in the implementation of supervision of the Child Friendly Green Open Space by the Gresik Regency Government was carried out by the Licensing Service as a gateway, by verifying consisting of two verification teams of industrial companies and housing development based on recommendations from the Department of the Environment through environmental documents that were has been made if there is a third party that does not carry out its obligations the Office of the Environment can provide a warning letter by requesting a copy to the Regent and the Licensing Office. Then related to controlling the existence of Child Friendly Green Open Space will be carried out by the Office of the Environment.